SPIRITUALITY IN ISLAMIC ENTREPRENEURSHIP: MOTIVATIONAND ACHIEVEMENTS OF SUCCESSFUL ENTREPRENEURS IN KELANTAN - Mubarak, Mohd Zain; Abd. Rahman, Asyraf; Yaacob, Mohd Rafi (Journal of Techno-Social, 2014)
Spirituality is a vital aspect in the context of Islamic entrepreneurship. In fact, the Malay entrepreneur’s achievement that associated with their attitude as one of the influential factors in many extents, is derived from internal religious values as a final solution. However, there is little studies that scrutinizing this issue extensively in the context of the entrepreneurs success. Therefore, this research will explore spiritual aspects by identifying the related characteristics and the significance from motivational view and achievements that would lead to the success in entrepreneurship. Through an in-depth interview and thematic analysis, it can be said that the characteristics and spiritual practice do influence the motivation of entrepreneurs to build confidence and perseverance. Holding tight to the moral principles and assisting to more efficient managerial aspects and the undertakings will lead to the success in the business endeavour.